Jezikovnostilne razlike in sorodnosti v govoru ruskega in slovenskega politika - Kopač, Barbara (Teorija in praksa, 2020)
The article aims to identify the linguistic styles used in political speeches in order to form political messages. Based on analysis of two speeches, one in the Slovenian and the other in the Russian language, we may conclude that both speakers like to use linguistic figures with influence power (repetition, verb aspect, verb modality and so on). Differences in their speeches are mostly visible in the use of different grammatical persons. When they wish to objectify and emphasise their grandness, they both use third-person singular, if they desire to underline co-responsibility, they use first-person plural, and when their intention is to point out their own importance, they use first-person singular. The latter is used in Russian speeches more often than in Slovenian ones.
Keywords: jezikovni stili; Political communication; Political language; Politics; politični govor; Politični jezik; Politično komuniciranje; Politiki; ruski politiki; slovenski politiki; Stilistika; Stylistics